ETHANOL EXTRACT OF SRIKAYA LEAF (ANNONA SQUAMOSA L.) AGAINST DIARRHEA - Hamdan (Journal of Holistic and Traditional Medicine, 2021)
Diarrhea with bowel disorders (BAB) that has bowel movements more than 3 times a day with a liquid consistency, can be supplemented with blood or mucus. Herbal medicine is classified as safe and effective, where there are only a few side effects when compared to synthetic drugs. Srikaya plant (Annona squamosa L.) is one of the plants traditional medicine and proven to have various properties. Roots, leaves, fruit, seeds and srikaya bark has many uses. This herb is traditionally used for the treatment of epilepsy, dysentery, heart problems, worm infections, bleeding, bacterial infection, and fever.